A novel peptide isolated from Catla skin collagen acts as a self-assembling scaffold promoting nucleation of calcium-deficient hydroxyapatite nanocrystals. (9th December 2022) - Asokan, Vishwadeep; Yelleti, Geethika; Bhat, Chetna; Bajaj, Mayur; Banerjee, Pradipta
Abstract: Catla collagen hydrolysate (CH) was fractionated by chromatography and each fraction was subjected to HA nucleation, with the resultant HA-fraction composites being scored based on the structural and functional group of the HA formed. The process was repeated till a single peptide with augmented HA nucleation capacity was obtained. The peptide (4.6 kDa), exhibited high solubility, existed in polyproline-II conformation and displayed a dynamic yet stable hierarchical self-assembling property. The 3D modelling of the peptide revealed multiple calcium and phosphate binding sites and a high propensity to self-assemble. Structural analysis of the peptide-HA crystals revealed characteristic diffraction planes of HA with mineralization following the (002) plane, retention of the self-assembled hierarchy of the peptide and intense ionic interactions between carboxyl groups and calcium. The peptide-HA composite crystals were mostly of 25–40 nm dimensions and displayed 79% mineralization, 92% crystallinity, 39.25% porosity, 12GPa Young's modulus and enhanced stability in physiological pH. Cells grown on peptide-HA depicted faster proliferation rates and higher levels of osteogenic markers. It was concluded that the prerequisite for HA nucleation by a peptide included: a conserved sequence with a unique charge topology allowing calcium chelation and its ability to form a dynamic self-assembled hierarchy for crystal propagation. Graphical Abstract: